Urbanization and Non-communicable disease mortality in Thailand: An ecological correlation study - Chaisiri Angkurawaranon (2018)
This study provides strong evidence from an LMIC that urbanization is associated with mortality from three lifestyle-associated diseases at an ecological level. Furthermore, our data suggest that both average household income and number of doctors per population are important factors to consider in ecological analyses of mortality. © 2012 Blackwell Publishing Ltd.